7-Step PBL: Problem Solving Ability of Students in Work and Energy - Amin Mustajab; Samsul Bahri; Ya Julyanto (STKIP Singkawang, 2020)
The purpose of this study was to determine the level of problem solving skills of students in the 7-Step PBL material work and energy materials. The method used in this research is descriptive method. The number of samples used in this study were 62 students. The data analysis technique used is descriptive analysis technique. There are three main findings in this study, the first amounted to 69.35% the average level of problem solving abilities of students is still at level 2 (moderate). Second, even after participating in learning using the 7-Step PBL method, the average problem solving ability of students has not yet reached level 4(high). Third, in indicator problem number 2